Peroxisome Proliferator-Activated Receptor-δ Deficiency in Microglia Results in Exacerbated Axonal Injury and Tissue Loss in Experimental Autoimmune Encephalomyelitis - Doroshenko, Ellinore R.; Drohomyrecky, Paulina C.; Gower, Annette; Whetstone, Heather; Cahill, Lindsay S.; Ganguly, Milan; Spring, Shoshana; Yi, Tae Joon; Sled, John G.; Dunn, Shannon E. (Frontiers in Immunology, 2021)
Peroxisome proliferator-activated receptor (PPAR)-δ is a nuclear receptor that functions to maintain metabolic homeostasis, regulate cell growth, and limit the development of excessive inflammation during immune responses. Previously, we reported that PPAR-δ-deficient mice develop a more severe clinical course of experimental autoimmune encephalomyelitis (EAE); however, it was difficult to delineate the role that microglia played in this disease phenotype since PPAR-δ-deficient mice exhibited a number of immune defects that enhanced CNS inflammation upstream of microglia activation. Here, we specifically investigated the role of PPAR-δ in microglia during EAE by using mice where excision of a floxed Ppard allele was driven by expression of a tamoxifen (TAM)-inducible CX3C chemokine receptor 1 promoter-Cre recombinase transgene (Cx3cr1CreERT2: Ppardfl/fl). We observed that by 30 days of TAM treatment, Cx3cr1CreERT2: Ppardfl/fl mice exhibited Cre-mediated deletion primarily in microglia and this was accompanied by efficient knockdown of Ppard expression in these cells. Upon induction of EAE, TAM-treated Cx3cr1CreERT2: Ppardfl/fl mice presented with an exacerbated course of disease compared to TAM-treated Ppard fl/fl controls. Histopathological and magnetic resonance (MR) studies on the spinal cord and brains of EAE mice revealed increased Iba-1 immunoreactivity, axonal injury and CNS tissue loss in the TAM-treated Cx3cr1CreERT2: Ppardfl/fl group compared to controls. In early EAE, a time when clinical scores and the infiltration of CD45+ leukocytes was equivalent between Cx3cr1CreERT2: Ppardfl/fl and Ppardfl/fl mice, Ppard-deficient microglia exhibited a more reactive phenotype as evidenced by a shorter maximum process length and lower expression of genes associated with a homeostatic microglia gene signature. In addition, Ppard-deficient microglia exhibited increased expression of genes associated with reactive oxygen species generation, phagocytosis and lipid clearance, M2-activation, and promotion of inflammation. Our results therefore suggest that PPAR-δ has an important role in microglia in limiting bystander tissue damage during neuroinflammation.